English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

Let's say A had x amount of p at first
and B had y amount of p at first

Then x = 2/3 y
and x+8 = 4/5 (y-5)

x+8 = 4/5 y - 4
x = 4/5 y - 4 - 8
= 4/5 y - 12

x = 2/3 y = 4/5 y - 12

Therefore 2/3 y = 4/5 y - 12
Make them the same denominators:
10/15 y = 12/15 y - 12
2y = 12
y = 6
x = 2/3 (6)
=4

Thus, A had 4p at first

2006-09-29 20:55:02 · answer #1 · answered by Ashley 2 · 0 0

Let at first A have x p and B y p

So, x-y = 2/3

x+8 -(y-5) = 4/5

or x-y = 4/5-13

2006-09-30 03:52:50 · answer #2 · answered by ag_iitkgp 7 · 0 0

2/3?

2006-09-30 03:49:30 · answer #3 · answered by Emily 3 · 0 0

fedest.com, questions and answers